2016
DOI: 10.5539/gjhs.v9n3p109
|View full text |Cite
|
Sign up to set email alerts
|

Anemia Related Mortality in Inner Mongolia in 2008–2012

Abstract: Objective: This study aimed to assess the characteristics of anemia-related deaths and the relationship between socio-demographic status and mortality risk of anemia in Inner Mongolia from 2008 to 2012. Methods:We obtained our data for 2008-2012 from the Death Registry System of Inner Mongolia. We calculated the mortality, percentage, and potential years of life lost (PYLL) of anemia in diseases of the blood and blood-forming organs and certain disorders involving the immune mechanism (DBDIM). We collected soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Our result indicated that pancreatic cancer mortality rate was increasing with aging for both genders. The global temporal trends are increasing significantly with age increasing [3] [11]. More population had pancreatic cancer at the age of 60 -65 and the age of 70 -80 years were up to the peak [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our result indicated that pancreatic cancer mortality rate was increasing with aging for both genders. The global temporal trends are increasing significantly with age increasing [3] [11]. More population had pancreatic cancer at the age of 60 -65 and the age of 70 -80 years were up to the peak [17].…”
Section: Discussionmentioning
confidence: 99%
“…The illiterate was defined the person who can't read and literacy. Primary school was defined a person who accepts formal education of initial stage, length of schooling is six years [11]. 2014, the mortality rate of pancreatic cancer in men was higher than that in women.…”
Section: Data Collectionmentioning
confidence: 99%